Evolution and Influence of Multivortex Structure on the Head of Canard-Controlled Missile at High Angle of Attack - Kai Wei; Shaosong Chen; Dongdong Tang; Yihang Xu; Xujian Lyu; Qing Chen (International Journal of Aerospace Engineering)
The issue of uncertain roll angle and large angle of attack during the initial stage of launch has a significant impact on the initial attitude and control of canard-controlled missiles. In this study, canard-controlled missiles are employed to study the influence of multivortex structure present in the head under different roll angles at high angles of attack. The turbulence model was verified and used for simulation. The evolution of the multivortex structures behind the canard and their impact on the flow field and lateral force was investigated. The results show that the multivortex structure at the head forms a flow field structure dominated by two main vortices through vortices merging. When the geometry is symmetric, the symmetric vortices maintain a long symmetry region on the flow field, and the “X” shape shows higher flow field stability than the “+” shape. The asymmetric geometric structure produces two asymmetric main vortices, causing alternating steady separation and shedding of downstream vortices. This leads to alternating pressure fluctuations on the surface of the body, which are reflected in the lateral force through the integration of the pressure along the lateral direction. In contrast to the alternating shedding of separation vortices observed in a wingless configuration due to natural asymmetry, the asymmetrical main vortices induced by the asymmetry of canard cause alternant vortex shedding to occur earlier. With the increase of the angle of attack, the pressure difference of the head gradually dominated the lateral force, resulting in a drastic decrease in the lateral force coefficient.